Population control of the mosquito Aedes aegypti in Santa Catarina - Brazil: perception of municipal and state managers (Revista Contexto & Saúde, 2025)
The aim of the study was to analyze, from the perspective of municipal and state managers, the effectiveness of policies and practices in controlling Aedes aegypti in Santa Catarina State. A semi-structured interview was conducted with the manager of Health Surveillance - Ae. aegypti control of the Santa Catarina State and managers of municipal vector control programs in the west of the state. There were difficulties in implementing the National Dengue Control Program (PNCD), considering the limitations of the work of the Endemic Disease Control Agent (ACE). Medical certificates, job deviations, absenteeism and turnover of these workers are among the problems. Health education for the community should be carried out in an intersectoral way, allied to the work of the ACEs in controlling Ae. aegypti. This study contributes to improving the possibilities of strategies, practices and policies for controlling Ae. aegypti used in Santa Catarina and Brazil.
Keywords: arboviruses; public health; vector control